Comparison of solutions to the task of IT product configuration items early identification using hierarchical clusterization methods - Ievlanov, Maksym; Vasiltcova, Nataliya; Panforova, Iryna; Moroz, Borys; Martynenko, Andrii; Moroz, Dmytro (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the IT project configuration management process. During the research, the problem of early identification of configuration items (CI) in the information system (IS) of enterprise management was solved. Research in this field is mainly aimed at solving the task of early identification of services and microservices during the refactoring of software systems. The issue of the application of artificial intelligence methods for the detection of CI has not been sufficiently investigated. During the study, the Chameleon hierarchical clustering method was adapted to solve the problem of early identification of CI IS. This method takes into account both the internal similarity and the connectivity of individual functions of the studied IS. The adapted Chameleon method was used when solving the task of early identification of CI in the functional task "Formation and maintenance of an individual plan of a scientific and pedagogical employee of the department". 10 functions and 12 essences of the problem database were considered as the initial CIs. The result of the solution is a dendrogram with all possible options for decomposition of the description of the task architecture into individual CIs. Based on the results, a comparative analysis of the use of Chameleon, DIANA, and AGNES methods for solving the problem of early identification was carried out. According to the criteria "Number of vertices of the dendrogram", "Number of levels of decomposition of the dendrogram", and "Evenness of filling the elements of the dendrogram", the results from using the Chameleon method are the best. Using the research results allows automating the procedure of forming backlogs of IT project implementation teams. This makes it possible to improve the quality of IS development by assigning IS containing similar functions to the same IT project executor